Posisi St. Maximus Pengaku Iman tentang Primasi Uskup Roma - Raditio, Klaus Heinrich (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2025)
Abstract: The primacy of the Bishop of Rome in the universal Church has been a topic of contention among Christians throughout history. For some, the authority of the Bishop of Rome creates a barrier that discourages Christian unity. The belief that Roman Catholics consider essential to Christian Tradition is seen by some as a mere man-made construct. This writing aims to discuss the thoughts of Maximus the Confessor (580-662), a Church Father and a central figure in the Byzantine Tradition. The central argument of this study is that Maximus the Confessor believed in Christ’s assurance to Peter regarding the guardianship of the Church until the end of time, as stated in the Gospel of Matthew. The authority of the Pope, which has developed throughout history, finds its source in the orthodox, universal, and apostolic faith. Keywords: Maximus; Patristic; orthodox; Peter; Bishop of Rome Abstrak: Primasi Uskup Roma di antara para uskup dalam gereja universal menjadi salah satu topik perdebatan di antara para pengikut Kristus. Bagi beberapa kalangan, posisi Paus atau Uskup Roma menjadi hal yang menghambat persatuan umat Kristen. Posisi Uskup Roma yang bagi umat Katolik Roma adalah sesuatu yang berkembang dari Tradisi Kristen dianggap semata-mata karangan manusia. Tulisan ini berusaha mengangkat pemikiran Maximus Pengaku Iman (580-662), seorang Bapa Gereja sekaligus Figur sentral dalam Tradisi Byzantine. Argumen tulisan ini adalah Maximus Pengaku Iman mengakui bahwa jaminan Kristus kepada Petrus untuk menjaga GerejaNya hingga akhir zaman seperti tertulis dalam Injil Matius. Posisi Paus yang berkembang hingga zaman ini bersumber dari iman yang ortodoks, universal dan apostolik. Kata kunci: Maximus; Patristik; orthodoks; Petrus; Uskup Roma